Technologies and practices for agriculture and food system adaptation to climate change in The Gambia - Segnon, Alcade C; Zougmoré, Robert B.; Houessionon, Prosper (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Agriculture is a major source of livelihood and income in The Gambia. Despite its socioeconomic importance, the sector faces many institutional, technological, and biophysical challenges limiting its contribution to economic development. The situation is exacerbated by adverse effects of climate change, which is undermining national efforts, making The Gambia one of the most vulnerable to climate change. This report documents and synthesizes available climate-smart agriculture (CSA) options that can inform adaptation planning in The Gambian agriculture and food system. We analysed the relevance of the documented options in sustainably increasing productivity and income while building climate resilience and reducing GHGs emissions in food systems. Through a mixed approach integrating multiple sources, a total of 28 technologies and practices has been identified as relevant adaptation options for The Gambia agriculture and food system. These options are grouped into nine adaptation categories including Crop diversity use and management, Soil and nutrient management, Soil & Water Conservation and Irrigation, Agroforestry systems, Livestock-based systems, agro-climatic information services, Social network and institutional support, and Livelihood diversification. Except for post-failure coping strategies known to be ineffective and unsustainable, all the identified options have some potentials to sustainably increase agricultural productivity and income while adapting and building resilience to climate change and reducing greenhouse gas emissions. This synthesis provides evidence of potential climate-smartness of the selected adaptation options and could be important to inform adaptation planning and prioritization.